Preparation of Pt-Zeolite Catalyst for Conversion of n-Octanol - I Made Sadiana; Iip Izul Falah; Triyono Triyono (Universitas Gadjah Mada, 2001)
Pt-zeolite catalyst has been prepared by immersing a sample of zeolite in PtCl4 solution. After separation, the sample was dried and calcinated at 550 °C for 4 hours under nitrogen stream. Furthermore, the sample was oxidized with oxygen gas at 350 °C for 2 hours and reduced with hydrogen gas at 400 °C for 2 hours. Total amount of impregnated metal, acidity and surface are of the samples were determined by using atomic absorption spectrophotometric, gravimetric and gas sorption methods, respectively. The activity test was done in a fixed bed reactor and the results of the reaction were analyzed by using gas chromatograph. The result of the characterization showed that the higher total amount of impregnated metal, the lower the surface area and total volume of pores. The acidity and the catalyst activity increase with the increasing of the total amount of impregnated metal. The flow rate of feed and temperature reaction also influence yield conversion. The optimum yield of n-octanol conversion was obtained at 400 °C with the showest flow rate of n-octanol and flow rate of H2 gas was equal to 40 mL/minute.